The Use of Diuretics in Kidney Transplantation: The Effects of Mannitol vs. Furosemide in Kidney Transplantation - رستم فاتن (Latakia University Journal -Medical Sciences Series, 2021)
تعتبر جراحة زرع الكلية الحل النهائي لعلاج مشكلة القصور الكلوي في مراحلة المتقدمة